Experimental Research on Influence of Noise-proof Earplugs on Miners’Safety Behavior - TIAN Shuicheng, SUN Luyao (Meikuang Anquan, 2020)
To explore the influence of noise-proof earplugs on the safety behavior of miners, through simulating the downhole noise environment,15 experimental subjects with bare ears or wearing earplugs were tested by using Mind Ware Bio Lab physiological indicator tester and multiple reaction time tester. The SPSS22.0 software was used to analyze the paired sample T test and linear regression analysis of the experimental data. Then, the individual behavior ability index of miner’s wearing earplugs was calculated. The results showed that there were significant differences in the data when wearing earplugs and bare ears. The individual behavior ability index of the 11 experimental subjects(15 in total) is less than 0. It is believed that the noise-proof earplugs have a certain protective effect on the miners, and it improves the safety behavior of the personnel, but reduces the ability of the person to respond to the sound.